Air plasma treatment of liquid covered tissue: long timescale chemistry. (22nd September 2016) - Lietz, Amanda M; Kushner, Mark J
Abstract: Atmospheric pressure plasmas have shown great promise for the treatment of wounds and cancerous tumors. In these applications, the sample is usually covered by a thin layer of a biological liquid. The reactive oxygen and nitrogen species (RONS) generated by the plasma activate and are processed by the liquid before the plasma produced activation reaches the tissue. The synergy between the plasma and the liquid, including evaporation and the solvation of ions and neutrals, is critical to understanding the outcome of plasma treatment. The atmospheric pressure plasma sources used in these procedures are typically repetitively pulsed. The processes activated by the plasma sources have multiple timescales—from a few ns during the discharge pulse to many minutes for reactions in the liquid. In this paper we discuss results from a computational investigation of plasma–liquid interactions and liquid phase chemistry using a global model with the goal of addressing this large dynamic range in timescales. In modeling air plasmas produced by a dielectric barrier discharge over liquid covered tissue, 5000 voltage pulses were simulated, followed by 5 min of afterglow. Due to the accumulation of long-lived species such as ozone and N x O y, the gas phase dynamics of the 5000th discharge pulse are different from those of the first pulse, particularly with regards to the negative ions. The consequences of applied voltage, gas flow, pulse repetition frequency, and the presence of organic molecules in the liquid on the gas and liquid reactive species are discussed.